Organizational issues in stroke treatment: The Swiss paradigm - Stroke units - Georgios K Matis (Journal of Neurosciences in Rural Practice, 2013)
Stroke represents the leading cause of acquired disability in adults and poses a tremendous socioeconomic burden both on patients and the society. In this sense, prompt diagnosis and urgent treatment are needed in order to radically reduce the devastating consequences of this disease. Herein the authors present the new guidelines recently adopted by the Swiss Stroke Society concerning the establishment of stroke units. Standardized treatment and allocation protocols along with an acute rehabilitation concept seem to be the core of the Swiss stroke management system. Coordinated multidisciplinary care provided by specialized medical, nursing and therapy staff is of utmost importance for achieving a significant dependency and death reduction. It is believed that the implementation of these guidelines in the stroke care system would be beneficial not only for the stroke patients, but also for the health system.